Tattershall Castle: building a history - Wright, James Peter (2022)
Tattershall Castle in Lincolnshire, United Kingdom, was developed in the 1230s for the regional baron, Robert de Tateshale. It was later remodelled, in the fifteenth century, for Ralph Lord Cromwell as a major expression of his status as a royal councillor and Lord Treasurer of England. The castle consists of three wards surrounded by water-filled moats which contained five gatehouses, several lodging ranges, chapel, services, hall, solar and Great Tower. The latter dominates the entire site and originally acted as an architectural focus which was imbued with motifs connected to Cromwell’s prestige.